Critically Examining the Conceptualisations of Language and Literacy in the National Curriculum Frameworks - Rawat, Aabha; Singh, Sunita (Voices of Teachers and Teacher Educators, 2023)
The purpose of this paper is to examine the conceptualisations of language and literacy in the National Curriculum Framework for Foundational Stage (2022) and National Curriculum Framework for School Education (2023) developed in consonance with the National Education Policy, 2020 (NEP 2020). The criticality of early literacy and numeracy leveraged on the pedagogical and transactional aspects of the same, are a major focus of the documents among other areas of early childhood care and education. The analysis is organised around the conceptualisations of Foundational Literacy in the NEP and the curriculum frameworks, analysis of the curricular contexts in the curricular frameworks and assessment and learning. It points to three conceptual shifts that have majorly shaped literacy pedagogy in the documents, an emphasis on comprehension, an understandingofliteracy from a developmental perspective, and a focus on a balanced view of literacy for pedagogical implementation. The paper suggests a more nuanced understanding of language and literacy which is organically connected with the sociocultural context and enables learners to critically examine the relevance of literacy in their lives. It also points to the need for more concerted efforts across stakeholders in order to accomplish the agenda set by NEP 2020 for Foundational Literacy